Distributed Agency in the Novel - Tenen, Dennis Yi (New literary history, 2023)
In this study, I propose to side-step the philosophical complexity surrounding free will, agency, or volition in favor of their linguistic proxy, syntax. Whatever the belief about willful subjects, the English language forces our thoughts into linear propositions, where subject verbs object. As such, nouns in the subject position become semantically the causes of action, and objects their passive effects: pilots fly planes, maintenance crews clean snow, terrorists detonate bombs. Such complex personifications don't need to be mapped out perfectly before observing that actors are those entities that act, and that action manifests itself through verbs. Assuming little more than that, one can ask: What sorts of nouns get to "do" stuff in the novel? Who are the most common syntactical actants? And who or what do they act upon? With this bit of shorthand we can discuss characterization not in terms of contested philosophical categories, such as name or being, but in relation to specific grammatical features. The syntactic points to the philosophical subject. I proceed, then, by developing a computational method for extracting a set of main characters from a novel (or any other collection of sentences in which agency might be implicated). Hailey's Airport bears the brunt of my analysis, where a few other more familiar novels supply comparison for an experiment in formal literary method.